Mitochondrial heteroplasmy improves risk prediction for myeloid neoplasms - Yun Soo Hong; Sergiu Pasca; Wen Shi; Daniela Puiu; Nicole J. Lake; Monkol Lek; Meng Ru; Megan L. Grove; Anna Prizment; Corinne E. Joshu; Elizabeth A. Platz; Eliseo Guallar; et al. (Nature Communications)
Abstract Clonal hematopoiesis of indeterminate potential is the primary pathogenic risk factor for myeloid neoplasms, while heteroplasmy (mutations in a subset of cellular mitochondrial DNA) is another marker of clonal expansion associated with hematological malignancies. We explore how these two markers relate and influence myeloid neoplasms incidence, and their role in risk stratification. We find that heteroplasmy is more common in individuals with clonal hematopoiesis of indeterminate potential, particularly those with higher variant allele fractions, multiple mutations, or spliceosome machinery mutations. Individuals with both markers have a higher risk of myeloid neoplasms than those with either alone. Furthermore, heteroplasmic variants with higher predicted deleteriousness increase the risk of myeloid neoplasms. Incorporating heteroplasmy in an existing risk score model for individuals with clonal hematopoiesis of indeterminate potential significantly improves sensitivity and better identifies high-risk groups. This suggests heteroplasmy as a clonal expansion marker and potentially as a biomarker for myeloid neoplasms development.